2022
DOI: 10.1002/mmce.23245
|View full text |Cite
|
Sign up to set email alerts
|

A compact planar dual band two‐port MIMO antenna with high isolation and efficiency

Abstract: A dual-band two-port MIMO antenna with high isolation and efficiency is proposed in this article. Each antenna element is composed of a rotated U-shaped strip and an L-shaped strip. The MIMO antenna is optimized to operate in 2.5-2.7 GHz and 4.8-5 GHz, which can cover the 5G bands of China Mobile. The defected ground structure consists of a slant square loop with a T-shaped slit and a U-shaped slot. A rectangle parasitic strip is placed in the U-shaped slot. The use of defected ground structure and parasitic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A Meta surface-based decoupling method is suggested in [25] to reduce the mutual couplings between the patches operating at two separate bands. A MIMO antenna consisting of a tilting square loop with a U-slot embedded in the defected ground is reported in [26]. Moreover, in a U-shaped slot, a rectangular metallic patch is fitted to achieve good isolation.…”
Section: Introductionmentioning
confidence: 99%
“…A Meta surface-based decoupling method is suggested in [25] to reduce the mutual couplings between the patches operating at two separate bands. A MIMO antenna consisting of a tilting square loop with a U-slot embedded in the defected ground is reported in [26]. Moreover, in a U-shaped slot, a rectangular metallic patch is fitted to achieve good isolation.…”
Section: Introductionmentioning
confidence: 99%
“…The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances. DGS has several advantages on the circuit [12], unwanted frequency suppression [13]- [15], bandwidth enhancement of antennas [16], [17], size compactness [18], [19], high power handling capability [20], isolation in antenna designs [21]- [23], and compensating parasitic capacitance of switching element to improve isolation [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple input-multiple output (MIMO) technology possesses promising application prospects in improving the data rate. Recently, many sub-6 GHz 5G smartphone MIMO antennas have been developed [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], such as four-element MIMO antennas [2][3][4][5], eight-port smartphone antennas [6][7][8][9][10], and even twelve-element MIMO antennas [11,12]. One nonnegligible challenge encountered during the design process is the method to effectively weaken the mutual electromagnetic coupling between antenna elements in a MIMO antenna array.…”
Section: Introductionmentioning
confidence: 99%
“…One nonnegligible challenge encountered during the design process is the method to effectively weaken the mutual electromagnetic coupling between antenna elements in a MIMO antenna array. However, numerous decoupling mechanisms have been put forward, such as polarization diversity [9], defected ground structure (DGS) [12,13], decoupling branches [14], neutralization lines [15], and orthogonal mode [16]. More attention still needs to be focused on the decoupling design in the MIMO antenna array.…”
Section: Introductionmentioning
confidence: 99%